Pengaruh Sikap Kerja Kualitas Kehidupan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Padang Lawas - Abdollah Harahap; Suryadi Suryadi; Romi Fahriza; Iska Latifah (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
The problems of this research is how much influence job attitude on employees performance. How much influence quality work of life on employees performance. How much influence job motivation on employees performance. How much influence job attitude, quality work of life and job motivation on employees performance. The purpose of this research is for know influence and analize of quality job attitude on employees performance. For know influence and analize of quality work of life on employees performance. For know influence and analize of job motivation on employees performance. For know influence quality work of life, job attitude and job motivation on employees performance. The sample in this research is 30 employees, with data analysis technique used is multiple linear regression analysis. The research result job attitude effect positive and significanly on employees performance. Quality work of life effect positive and significanly on employees performance. Job motivation effect positive and significanly to employees performance. Job attitude, quality work of life and job motivation effect positive and significanly to employees performance.